2017
DOI: 10.4149/neo_2017_610
|View full text |Cite
|
Sign up to set email alerts
|

The E3 ubiquitin ligase Cbl-b inhibits tumor growth in multidrug-resistant gastric and breast cancer cells

Abstract: Most receptor tyrosine kinases (RTKs) contribute to tumor growth, and their ubiquitination and degradation is related to the inhibition of tumor growth. Our previous study showed that the ubiquitin ligase Cbl-b was expressed at low levels in multidrug-resistant (MDR) gastric cancer cells compared with their parental cells. However, whether enhancement of Cbl-b expression in MDR cancer cells could prevent tumor proliferation via ubiquitination and degradation of RTK remains unclear. In the present study, Cbl-b … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…As consistent findings in lung and gastric cancers, suppression of cell proliferation was applied by Cbl‐b through ubiquitination of the EGFR pathway [154]. Similarly, inhibition of tumor cell proliferation by Cbl‐b was also shown in breast cancers [155]. Of interest, it was shown in a report [155] that the positive expression of Cbl‐b can be considered an appropriate prognostic predictor in breast cancer, mainly in cases with lymph node metastasis and stages II–III.…”
Section: Cbl‐b In Immune‐related Diseasessupporting
confidence: 61%
See 1 more Smart Citation
“…As consistent findings in lung and gastric cancers, suppression of cell proliferation was applied by Cbl‐b through ubiquitination of the EGFR pathway [154]. Similarly, inhibition of tumor cell proliferation by Cbl‐b was also shown in breast cancers [155]. Of interest, it was shown in a report [155] that the positive expression of Cbl‐b can be considered an appropriate prognostic predictor in breast cancer, mainly in cases with lymph node metastasis and stages II–III.…”
Section: Cbl‐b In Immune‐related Diseasessupporting
confidence: 61%
“…Similarly, inhibition of tumor cell proliferation by Cbl‐b was also shown in breast cancers [155]. Of interest, it was shown in a report [155] that the positive expression of Cbl‐b can be considered an appropriate prognostic predictor in breast cancer, mainly in cases with lymph node metastasis and stages II–III.…”
Section: Cbl‐b In Immune‐related Diseasesmentioning
confidence: 96%
“…We have found that Cbl-b could inhibit cell proliferation by ubiquitinating the survival signal of the epidermal growth factor receptor (EGFR) pathway in lung (19,20) and gastric cancer cells (13,21,22). Also, previous studies showed that Cbl-b could inhibit tumor growth in some breast cancer cells (6,23). However, in other tumor types Cbl-b may promote the migration and proliferation of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Cbl-b was known to have a broad spectrum of biological functions and it regulates various signaling pathways in a cell type-dependent manner (Liyasova et al, 2015;Lutz-Nicoladoni et al, 2015). Cbl-b could inhibit proliferation of multidrug-resistant gastric and breast cancer cells (Che et al, 2017), promote shikonin-induced apoptosis in lung cancer cells (Qu et al, 2015). In addition, in our previous study, we found that Cbl-b was up-regulated during bufalininducing apoptosis in gastric cancer cells via inhibition of PI3K/Akt signaling pathway (Li et al, 2009).…”
Section: Discussionmentioning
confidence: 99%